Above-Average Rise in Immigrant Poverty: Poverty Often Concomitant with Other Types of Deprivation - Ingrid Tucci; Gert G. Wagner (Weekly Report, 2005)
The years 1998 to 2003 were marked by a deterioration in the economic situation of the German population with an immigrant background as the share of immigrants living below the poverty line increased at an above average rate. The older and younger age groups in this segment of the population are particularly prone to poverty. The Socio-Economic Panel (SOEP) survey, which is carried out by the DIW Berlin in collaboration with the Infratest Social Research Institute, shows that 28% of children and young people aged under 20 with an immigrant background were living in precarious circumstances in 2003. The share of native Germans of the same age living in such circumstances was substantially lower, albeit still disturbingly high at 20%. Citizens of Turkish origin, in particular, are frequently found living below the poverty line. Immigrants from Western countries, by contrast, live comparatively rarely in poverty. Naturalised Germans are better off on average than foreign nationals, although this is not true for ethnic Germans. The fact that poverty is not a transitory phenomenon but an enduring condition for many immigrants is particularly alarming. Only improved education and training will solve this problem in the long term. The recruitment of foreign labour, the admission of refugees and the return of ethnic German settlers from former Eastern Bloc countries have culminated in large waves of immigration to Germany over the last 50 years. On official figures, over seven million foreign nationals and over four million ethnic Germans are living in Germany today. Germany still has a net migration surplus, although it has diminished significantly in recent years.
Keywords: 330